Membrane attack complex generation increases as a function of time in stored blood. Issue 2 (4th March 2014) - Hu, X.; Patel, R. P.; Weinberg, J. A.; Marques, M. B.; Ramos, T. N.; Barnum, S. R.
SUMMARY Objective To determine if the complement system, a potent mediator of inflammation, contributes to haemolysis during red blood cell (RBC) storage. Background RBCs in storage undergo structural and biochemical changes that may result in adverse patient outcomes post‐transfusion. Complement activation on leukodepletion and during storage may contribute to the RBC storage lesion. Methods/Materials We performed a cross‐sectional analysis of aliquots of leukoreduced RBC units, stored for 1–6 weeks, for the levels of C3a, C5a, Bb, iC3b, C4d and C5b‐9 [membrane attack complex (MAC)] by enzyme‐linked immunosorbent assay (ELISA). Results We observed that only MAC levels significantly increased in RBC units as a function of storage time. We also observed that the level of C5b‐9 bound to RBCs increased as a function of storage time. Conclusion MAC levels increased over time, suggesting that MAC is the primary complement‐mediated contributor to changes in stored RBCs. Inhibition of the terminal complement pathway may stabilise RBC functionality and extend shelf life.